Origins and consequences of university desertion; mathematical model with the most frequent variables that can contribute to determining the profile of the student to drop out of school - Peña Chamorro, Libardo Ricaurte; Patiño Hernández, Luis Adolfo (Tierra Infinita, 2022)
The objective of this article is to determine the State of the Art of the origins and consequences of university desertion with a view to the elaboration of a mathematical model that contributes to determining the profile of the student dropout. The methodology consisted of the review of thirtysix (36) bibliographical references in which there are around a hundred international and national experts who give an account of how desertion originates in universities and what are the most impressive consequences. The results show that the causes of university dropout are multiple and are generally related to the limited economic resources of the student, the conflict between study and work, premature obligations acquired by the students, academic problems, maladjustments to adapt to university life. The limited help of the teacher in the tutorials, poor evaluation practice, the excessive amount of autonomous work, among others. The Article consists of five sections, in the first the origins of the dropout of university students are analyzed, in the second the consequences of the abandonment of the dropout, in the third a brief characterization of the mathematical model, in the fourth the variables that they can contribute to determining the profile of the student to drop out, and in the fifth the conclusions are specified.
Keywords: university dropout; mathematical model; dropout profile